2011
DOI: 10.1177/0266242610369945
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of small business Website optimization: Enablers, influencers and an assessment approach

Abstract: The literature reveals a need for more integrated research contributions to small business Internet adoption and theoretical development. There is also a need for these developments to relate more closely to effective, or optimized, use of web applications in business processes and growth. To address this, and building upon recent integrated theoretical developments, the aim of this study is to explore the determinants and outcomes relating to small business Website optimization. Five determining variables iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
94
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 101 publications
3
94
0
Order By: Relevance
“…In fact, a study of the changes in website content of 39 micro businesses (Burgess et al, 2007) showed little evidence of stage growth and that some businesses had actually removed features from their websites. Simmons et al (2011) suggested that subsequent to the development of stage models, 'contingent' models had been developed that recognise that different types of businesses will take different approaches to their online presence. The stage models presented thus far are inward looking in regards to a business website and do not consider external influences (such as the website strategy of competitors).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a study of the changes in website content of 39 micro businesses (Burgess et al, 2007) showed little evidence of stage growth and that some businesses had actually removed features from their websites. Simmons et al (2011) suggested that subsequent to the development of stage models, 'contingent' models had been developed that recognise that different types of businesses will take different approaches to their online presence. The stage models presented thus far are inward looking in regards to a business website and do not consider external influences (such as the website strategy of competitors).…”
Section: Introductionmentioning
confidence: 99%
“…A second form of KAA capabilities is e-commerce. As this capability is transactional in nature, it has become easier for SMEs to develop successfully [35]. E-commerce capability refers to the buying and selling of goods and services through the Internet and Web-based technologies [36].…”
Section: Kaa Capabilitiesmentioning
confidence: 99%
“…These tools were used to facilitate more formalized and structured approaches to understanding online customers. Simmons et al (2011) found that such tools complemented and supported online and offline the more informal type of marketing planning the small businesses studied would normally practice. They based this on small business competencies such as creativity, flexibility and intuitive judgment.…”
mentioning
confidence: 93%
“…Pelham and Wilson (1996) and Pelham (2000), indicate that the typically low levels of formalization in small businesses' marketing planning will not necessarily reduce the innovative and flexible aspects of their ways of achieving this. Recent work by Simmons et al (2011) suggests that an informal-formal synergy may exist in this regard. In a study of small business web site optimization they found that those firms at leading edge were positively influenced by using cost-effective web tools such as web analytics, online surveys, community forums and database technology.…”
mentioning
confidence: 99%